2017
DOI: 10.1111/2041-210x.12817
|View full text |Cite
|
Sign up to set email alerts
|

A trophic interaction framework for identifying the invasive capacity of novel organisms

Abstract: The likelihood and impacts of invasions by novel organisms (e.g. non‐native species, genetically modified organisms) on the composition and functioning of receiving biological communities hinges on their capacity to exploit resources and/or avoid predation relative to resident counterparts. While assessment of invasion risk based on the comparison of functional responses (per‐capita consumption rate as a function of resource density) of novel species with native analogues has been gaining popularity, it may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…, Penk et al. ). Some behavioral traits such as activity, aggressiveness, and boldness have repeatedly been associated with invasion success (Weis , Chapple et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Penk et al. ). Some behavioral traits such as activity, aggressiveness, and boldness have repeatedly been associated with invasion success (Weis , Chapple et al.…”
Section: Introductionmentioning
confidence: 99%
“…They can thus be used as comparator organisms sensu Penk et al. (): Comparing marbled crayfish to resident spiny‐cheek crayfish allows assessing the invasive capacity of marbled crayfish. Furthermore, both species are included in the List of Invasive Alien Species of Union Concern (EU Regulation 1143/2014).…”
Section: Introductionmentioning
confidence: 99%
“…Competition for food will influence interspecific aggression, and interference by predators affects activity and boldness (Pintor et al, ). Assessments like ours should therefore be extended by including higher‐order predators or direct competition (see Penk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vonesh, McCoy, Altwegg, Landi & Measey, 2017;Dick et al, 2017b,c), these experiments can provide a rapid impact assessment tool capable of predicting ecological impacts of invasive fishes and other non-native taxa (e.g. Alexander et al, 2014;Penk et al, 2017).…”
Section: Comparative Behavioural Functional Responsesmentioning
confidence: 99%
“…For example, they demonstrated that whilst consumption rates of individual invasive P. parva might be relatively low, their propensity for forming highly abundant populations means that when scaled up to population levels, their relative impact potential (Dick et al, 2017a) is substantially elevated and of high ecological concern. Indeed, the development of more nuanced experimental and analytical protocols for comparative functional responses for non-native fishes that are, for example, omnivorous and exploitative competitors, enables increased ecological complexity and realism within predictions, thus providing a more robust and powerful predictive tool (Dick et al, 2017a;Laverty et al, 2017;Penk et al, 2017).…”
Section: Comparative Behavioural Functional Responsesmentioning
confidence: 99%